Alleviating D-Galactose-Induced Aging in Mice by Modulating Gut-Liver Axis Using Lactiplantibacillus plantarum TY-Y10 - Shaoqi Shi; Xiaoxia Li; Feng Zhang; Zhengqiang Jiang; Jing Wang; Liang Zhao; Juan Chen; Xi Shu; Bing Fang; Ping Liu; Jingjing He; Shaoyang Ge; et al. (Foods)
Oxidative stress is closely linked to aging. Probiotics, whether viable or heat-inactivated, have shown antioxidant properties; however, their effect and mechanism of action in reducing oxidative stress during aging remains underexplored. This study examined the effects of viable and heat-inactivated Lactiplantibacillus plantarum TY-Y10 (L. plantarum TY-Y10) on D-galactose (D-gal)-induced aging in mice, aiming to uncover potential anti-aging mechanisms. Mice were induced to age with D-gal injections, then treated with sodium ascorbate (positive control) or varying doses of L. plantarum TY-Y10 for eight weeks. After treatment, oxidative stress markers, gut microbiota, and liver health were analyzed. Results showed that L. plantarum TY-Y10 decreased malondialdehyde (MDA) and inflammatory markers while increasing antioxidant levels (glutathione, superoxide dismutase, catalase and glutathione peroxidase). Liver damage was reduced, and expression of Nrf2 and related antioxidant enzymes improved. Additionally, L. plantarum TY-Y10 enhanced the abundance of short-chain fatty acid-producing bacteria, boosting fecal short-chain fatty acid levels. In short, both viable and heat-inactivated L. plantarum TY-Y10 mitigated oxidative stress in aging mice by modulating gut microbiota and activating liver antioxidant pathways through the gut-liver axis.